0\; ,\; \; >-1\\\\2^{log_3(9x+9)}=2^{log_26}\; \; \; \; \; \Big [\; a^{log_{a}b}=b\; ,\; \; a>0\; ,\; a\ne 1\; ,\; b>0\; \Big ]\\\\log_3(9x+9)=log_26\; \; \; \; \Big [\; log_{a}x=b\; \; \to \; \; x=a^{b}\; \Big ]\\\\9x+9=3^{log_26}\\\\9x=3^{log_26}-9\\\\x=\frac{1}{9}\cdot 3^{log_26}-1\\\\x=\frac{3^{log_26}}{3^2}-1\\\\\underline {x=3^{log_26-2}-1}\\\\x=3^{log_2(2\cdot 3)-2}-1\\\\x=3^{log_22-log_23-2}-1\\\\x=3^{1-log_23-2}-1\\\\\underline {x=3^{-log_23-1}-1}" alt="2^{log_3(9x+9)}=6\; ,\qquad ODZ:\; 9x+9>0\; ,\; \; >-1\\\\2^{log_3(9x+9)}=2^{log_26}\; \; \; \; \; \Big [\; a^{log_{a}b}=b\; ,\; \; a>0\; ,\; a\ne 1\; ,\; b>0\; \Big ]\\\\log_3(9x+9)=log_26\; \; \; \; \Big [\; log_{a}x=b\; \; \to \; \; x=a^{b}\; \Big ]\\\\9x+9=3^{log_26}\\\\9x=3^{log_26}-9\\\\x=\frac{1}{9}\cdot 3^{log_26}-1\\\\x=\frac{3^{log_26}}{3^2}-1\\\\\underline {x=3^{log_26-2}-1}\\\\x=3^{log_2(2\cdot 3)-2}-1\\\\x=3^{log_22-log_23-2}-1\\\\x=3^{1-log_23-2}-1\\\\\underline {x=3^{-log_23-1}-1}" align="absmiddle" class="latex-formula">
![P.S.\; \; x=3^{log_26-2}-1\\\\x=3^{\frac{log_36}{log_32}}\cdot 3^{-2}-1\\\\x=\Big (3^{log_36}\Big )^{\frac{1}{log_32}}\cdot \frac{1}{9}-1\\\\x=6^{log_23}\cdot \frac{1}{9}-1\\\\x=\frac{6^{log_23}}{9}-1 P.S.\; \; x=3^{log_26-2}-1\\\\x=3^{\frac{log_36}{log_32}}\cdot 3^{-2}-1\\\\x=\Big (3^{log_36}\Big )^{\frac{1}{log_32}}\cdot \frac{1}{9}-1\\\\x=6^{log_23}\cdot \frac{1}{9}-1\\\\x=\frac{6^{log_23}}{9}-1](https://tex.z-dn.net/?f=P.S.%5C%3B%20%5C%3B%20x%3D3%5E%7Blog_26-2%7D-1%5C%5C%5C%5Cx%3D3%5E%7B%5Cfrac%7Blog_36%7D%7Blog_32%7D%7D%5Ccdot%203%5E%7B-2%7D-1%5C%5C%5C%5Cx%3D%5CBig%20%283%5E%7Blog_36%7D%5CBig%20%29%5E%7B%5Cfrac%7B1%7D%7Blog_32%7D%7D%5Ccdot%20%5Cfrac%7B1%7D%7B9%7D-1%5C%5C%5C%5Cx%3D6%5E%7Blog_23%7D%5Ccdot%20%5Cfrac%7B1%7D%7B9%7D-1%5C%5C%5C%5Cx%3D%5Cfrac%7B6%5E%7Blog_23%7D%7D%7B9%7D-1)